Does front-of-pack nutrition information improve consumer ability to make healthful choices? Performance of warnings and the traffic light system in a simulated shopping experiment - Machín, Leandro; Aschemann-Witzel, Jessica; Curutchet, María Rosa; Giménez, Ana; Ares, Gastón (Appetite, 2018)
The inclusion of more attention-grabbing and easily interpretable front-of-pack (FOP) nutrition information is one of the public policies that can be implemented to empower consumers to identify unhealthful food products and to make more informed food choices. The aim of the present work was to evaluate the influence of two FOP nutrition labelling schemes – the traffic light labelling and the warning scheme – on consumer food purchases when facing a health goal. The study was conducted with 1182 people from Montevideo (Uruguay), recruited using a Facebook advertisement. Participants were randomly allocated to one of three between-subjects experimental conditions: (i) a control condition with no FOP nutrition information, (ii) FOP nutrition information using a modified version of the traffic light system including information about calorie, saturated fat, sugars and sodium content per portion, and (iii) FOP nutrition information using the Chilean warning system including separate signs for high calorie, saturated fat, sugars and sodium content. Respondents were asked to imagine that they had to purchase food in order to prepare a healthy dinner for themselves and their family, using the website of an online grocery store. Results showed that FOP nutrition information effectively improved the average healthfulness of participants’ choices compared to the control condition, both in terms of the average nutritional composition of the purchased products and expenditure in specific product categories. No relevant differences between the effect of the traffic light and the warning system were found.